Genetic polymorphisms in the CD14 gene are associated with monocyte activation and carotid intima-media thickness in HIV-infected patients on antiretroviral therapy - Yong, Y.K.; Shankar, E.M.; Westhorpe, C.L.V.; Maisa, A.; Spelman, T.; Kamarulzaman, A.; Crowe, S.M.; Lewin, S.R. (Lippincott, Williams & Wilkins, 2016)
HIV-infected individuals on antiretroviral therapy (ART) are at increased risk of cardiovascular disease (CVD). Given the relationship between innate immune activation and CVD, we investigated the association of single-nucleotide polymorphisms (SNPs) in TLR4 and CD14 and carotid intima-media thickness (cIMT), a surrogate measurement for CVD, in HIV-infected individuals on ART and HIV-uninfected controls as a cross-sectional, case-control study. We quantified the frequency of monocyte subsets (CD14, CD16), markers of monocyte activation (CD38, HLA-DR), and endothelial adhesion (CCR2, CX3CR1, CD11b) by flow cytometry. Plasma levels of lipopolysaccharide, sCD163, sCD14, sCX3CL1, and sCCL2, were measured by ELISA. Genotyping of TLR4 and CD14 SNPs was also performed. The TT genotype for CD14/-260SNP but not the CC/CT genotype was associated with elevated plasma sCD14, and increased frequency of CD11b+CD14+ monocytes in HIV-infected individuals. The TT genotype was associated with lower cIMT in HIV-infected patients (n = 47) but not in HIV-uninfected controls (n = 37). The AG genotype for TLR4/+896 was associated with increased CX3CR1 expression on total monocytes among HIV-infected individuals and increased sCCL2 and fibrinogen levels in HIV-uninfected controls. SNPs in CD14/-260 and TLR4/+896 were significantly associated with different markers of systemic and monocyte activation and cIMT that differed between HIV-infected participants on ART and HIV-uninfected controls. Further investigation on the relationship of these SNPs with a clinical endpoint of CVD is warranted in HIV-infected patients on ART.